A Role for Folate in Microbiome-Linked Control of Autoimmunity. (20th May 2021) - Mölzer, Christine; Wilson, Heather M.; Kuffova, Lucia; Forrester, John V.
Abstract : The microbiome exerts considerable control over immune homeostasis and influences susceptibility to autoimmune and autoinflammatory disease (AD/AID) such as inflammatory bowel disease (IBD), multiple sclerosis (MS), type 1 diabetes (T1D), psoriasis, and uveitis. In part, this is due to direct effects of the microbiome on gastrointestinal (GI) physiology and nutrient transport, but also to indirect effects on immunoregulatory controls, including induction and stabilization of T regulatory cells (T reg ). Secreted bacterial metabolites such as short-chain fatty acids (SCFA) are under intense investigation as mediators of these effects. In contrast, folate (vitamin B9), an essential micronutrient, has attracted less attention, possibly because it exerts global physiological effects which are difficult to differentiate from specific effects on the immune system. Here, we review the role of folate in AD/AID with some emphasis on sight-threatening autoimmune uveitis. Since folate is required for the generation and maintenance of T reg, we propose that one mechanism for microbiome-based control of AD/AID is via folate-dependent induction of GI tract T reg, particularly colonic T reg, via anergic T cells (T an ). Hence, folate supplementation has potential prophylactic and/or therapeutic benefit in AID/AD.